1992
DOI: 10.1039/dt9920002209
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structures of monomeric gallium trichloride, indium trichloride and lead tetrachloride by gas electron diffraction

Abstract: Gas electron diffraction data for monomeric GaCI,, monomeric InCI, and PbCI, have been recorded with nozzle temperatures of about 380,480 and 20 "C respectively. The data for GaCI, and InCI, are consistent with equilibrium structures of D,, symmetry and bond distances r, = 210.8(3) and 228.9(5) p m respectively. The data for PbCI, are consistent with an equilibrium structure of T, symmetry and r, = 237.3(3) pm. Bond energies and distances from the literature show that the M-CI bonds in MCI(g) are stronger, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 17 publications
5
18
0
1
Order By: Relevance
“…Both the Sc᎐Cl and La᎐Cl MBEs are larger than those of the Group 13 analogues, MCl 3 , M = B, Al, Ga or In, which range from 456 to 327 kJ mol Ϫ1 . 25 While the MBEs of the Group 13 trichlorides decrease as the group is descended, those of the Group 3 trichlorides appear to increase.…”
Section: Bond Energiesmentioning
confidence: 96%
See 1 more Smart Citation
“…Both the Sc᎐Cl and La᎐Cl MBEs are larger than those of the Group 13 analogues, MCl 3 , M = B, Al, Ga or In, which range from 456 to 327 kJ mol Ϫ1 . 25 While the MBEs of the Group 13 trichlorides decrease as the group is descended, those of the Group 3 trichlorides appear to increase.…”
Section: Bond Energiesmentioning
confidence: 96%
“…Before going on to discuss the molecular structures of the monomeric trichlorides of the heavier Group 3 metals, yttrium and lanthanum, we pause to note that while the bond distances in the Group 13 trichlorides MCl 3 , M = Al, Ga or In, are 6 to 11 pm shorter than the bond distance in the monochlorides MCl, 25 the bond distance in ScCl 3 is 6 pm longer than in ScCl, 222.9 pm. 26 An early GED investigation of YCl 3 indicated that the equilibrium structure is planar.…”
Section: The Molecular Structure Of Scclmentioning
confidence: 99%
“…In our study of PbCl, we found the gas to contain a mole fraction x of 0.19(3) gaseous Cl,. 29 The refinement of UCl, was therefore repeated with the mole fraction of C1, (with known bond distance and vibrational amplitude) as an additional adjustable parameter: the mole fraction was found to be x(C1,) = 0.21(4) and the R factor decreased to 0.0517.…”
Section: Gas Electron Diffraction-ifmentioning
confidence: 99%
“…These molecules get into the second part of the nozzle that is heated to a much higher temperature and where the dimers dissociate into monomers. This system has been used in our laboratory to determine the structure of, e.g., monomeric Group 13 trihalides [14,15] and other monomeric metal halides and also in the Oslo Electron Diffraction Group [16]. Finally, special high-temperature nozzle systems were developed for carrying out diffraction experiments on reactive and unstable species prepared during the diffraction experiments [17,18].…”
Section: High-temperature Gas-phase Electron Diffractionmentioning
confidence: 99%